Alkaline Earth Metallocenes Coordinated with Ester Pendants: Synthesis, Structural Characterization, and Application in Metathesis Reactions. Issue 38 (9th August 2013) - Li, Heng; Zhang, Wen‐Xiong; Xi, Zhenfeng
Abstract A variety of ester‐substituted cyclopentadiene derivatives have been synthesized by one‐pot reactions of 1, 4‐dilithio‐1, 3‐butadienes, CO, and acid chlorides. Direct deprotonation of the ester‐substituted cyclopentadienes with Ae[N(SiMe3)2]2 (Ae=Ca, Sr, Ba) efficiently generated members of a new class of heavier alkaline earth (Ca, Sr, Ba) metallocenes in good to excellent yields. Single‐crystal X‐ray structural analysis demonstrated that these heavier alkaline earth metallocenes incorporated two intramolecularly coordinated ester pendants and multiply‐substituted cyclopentadienyl ligands. The corresponding transition metal metallocenes, such as ferrocene derivatives and half‐sandwich cyclopentadienyl tricarbonylrhenium complexes, could be generated highly efficiently by metathesis reactions. The multiply‐substituted cyclopentadiene ligands bearing an ester pendant, and the corresponding heavier alkaline earth and transition‐metal metallocenes, may have further applications in coordination chemistry, organometallic chemistry, and organic synthesis.